Legal and Economic Aspects of Halal Product Certification in Indonesia: A Comparative Study of the Job Creation Law and the Halal Product Certification Law - Rustamunadi Rustamunadi; Hanafi Hanafi; Ikin Ainul Yakin; Ida Sulastri (Eduvest - Journal of Universal Studies, 2026)
This research is motivated by the increasing demand for halal product assurance in the context of global economic integration, consumer protection, and the enhancement of the competitiveness of the national halal industry within a value-based economic system. This study aims to comprehensively analyze the economic law aspects in the implementation of halal product assurance in Indonesia, with a particular focus on the transformation of the legal regime through a comparative approach between Law Number 33 of 2014 on Halal Product Assurance and Law Number 11 of 2020 on Job Creation along with its implementing regulations. This research employs a normative (doctrinal) legal research method, utilizing statutory, conceptual, and comparative approaches. The data sources consist of primary, secondary, and tertiary legal materials, which are analyzed qualitatively through systematic, grammatical, and teleological interpretation techniques to understand the direction and implications of legal norm development. The findings indicate that there has been a significant transformation in the halal product assurance legal regime, marked by amendments, additions, and reaffirmations of legal norms, including the simplification of halal certification procedures, the strengthening of institutional roles, and the acceleration of services oriented toward ease of doing business. From an economic law perspective, this condition highlights the necessity of a responsive, adaptive, and integrative legal policy capable of balancing economic interests, sharia values, and the principles of economic democracy as mandated by the constitution.